Profit management at Ukrainian enterprises in the context of post-industrial transformation of industry markets - Khatser, Maxim (Management and Entrepreneurship: Trends of Development, 2025)
The article is devoted to the formation of new scientific decisions on the study of the peculiarities of profit management at the enterprises of Ukraine in the conditions of post-industrial transformation of industry markets. The scientific and practical need to intensify the processes of improving profit management at Ukrainian enterprises, taking into account the acceleration of the transition processes of economic systems of different levels (global, international, national, regional, sectoral, local, enterprise groups, individual enterprises, and individual households) on a post-industrial development model. The aim of the article is to identify ways to enhance the efficiency of profit management at Ukrainian enterprises in the conditions of post-industrial transformation of industry markets. Methodology: a complex of general and special methods at the empirical and theoretical levels has been used. They include a method of literary analysis to determine the essence of the term "profit of the enterprise"; and an abstraction method for identifying differences at the level of national economic systems, sectoral markets, and business entities operating on the basis of industrial and post-industrial development models; methods of induction and deduction for the selection and characteristics of profit management elements in the enterprise, which need to be studied regarding the determination of differences in industrial and post-industrial models of development; methods of analysis and synthesis for the development of ways to improve the efficiency of profit management at Ukrainian enterprises in the conditions of transition of industry markets to a post-industrial model of development. Additionally, systematization, grouping, and logical generalization methods are used to structure information, draw conclusions, and develop scientific proposals. Results: The directions of ensuring the profitability of Ukrainian enterprises in the conditions of acceleration of the processes of transition of economic systems of different levels, including industry markets, on the post-industrial model of development have been revealed. JEL Classification: D21, D83, L10, M10